2007
DOI: 10.1093/hsw/32.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Grief in Terminal Illness and Bereavement: A Mixed-Methods Study

Abstract: Caregivers experience multiple losses during the downhill trajectory of a loved one's terminal illness. Using mixed methods, this two-stage study explored caregiver grief during a terminal illness and after the care recipient's death. Caregiver grief was a state of heightened responsiveness during end-stage care: anxiety, hostility, depression, and trouble concentrating, remembering, and getting things done. Following the death, caregiver grief became a state of sustained reactivity: Overall distress was dimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 20 publications
(17 reference statements)
2
63
0
3
Order By: Relevance
“…This result is the same as for Australian caregivers, 21 but in contrast to that for Canadian FCs. 7 However, as previously reported, 16,33 we found that the impact of EOL caregiving on Taiwanese FCs' schedule and health increased significantly as the terminally ill cancer patient's death came closer. As terminally ill cancer patients' physical condition deteriorates, 16 the caregiving impact on FCs' schedule obviously rises and the caregivers' physical health worsens and exhaustion appears.…”
Section: Discussionsupporting
confidence: 80%
“…This result is the same as for Australian caregivers, 21 but in contrast to that for Canadian FCs. 7 However, as previously reported, 16,33 we found that the impact of EOL caregiving on Taiwanese FCs' schedule and health increased significantly as the terminally ill cancer patient's death came closer. As terminally ill cancer patients' physical condition deteriorates, 16 the caregiving impact on FCs' schedule obviously rises and the caregivers' physical health worsens and exhaustion appears.…”
Section: Discussionsupporting
confidence: 80%
“…Rumination and seeking an understanding about causality are among non-adaptive coping behaviors that keep individuals stuck in the grief process (Lyubomirsky & Nolen-Hoeksema, 1993). Non-adaptive coping strategies also include feelings of despair, anger, loneliness, anxiety, sadness, crying, agitation, withdrawal, anxiousness, irritability, depression, numbness, shock, dissociation, sleep disturbance, decreased appetite, immune suppression leading to illness, decreased energy, somatic complaints, and exhaustion (American Psychological Association, 2000; Rando, 2000;Rosenzweig, Prigerson, Miller, & Reynolds, 1997;Silverberg, 2007;Stroebe, Hansson, Stroebe, & Schut, 2001;Waldrop, 2001).…”
Section: Non-adaptive Copingmentioning
confidence: 99%
“…Anticipatory grief affects caregivers physically, emotionally, and cognitively (Kehl, 2005;Waldrop, 2007). The physical manifestations of anticipatory grief include loss of appetite, insomnia, and exhaustion.…”
Section: Anticipatory Griefmentioning
confidence: 99%
“…Based on the continuing lack of resources available, stress continues to be a predominant emotional state that caregivers report experiencing while providing care (Anngela-Cole & Hilton, 2009;Savla et al, 2008;Waldrop, 2007).…”
Section: Introductionmentioning
confidence: 99%